The Influence of Syntax On Meaning In Poetry Reading - Ismahani, Siti; Fadhilah, Nurul; Batubara, Putri Fadilah; Fadlan, Fadlan; Salmanda, Dandi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In this our observation of research with title â€˜English Syntax Effect Meaning Through Poetryâ€ we are considering to observe the research of our topic above. This write goals to observe and attract students interest of poetry. This topic also direct students to ask students comprehension of English literary. This observation based on study on students tho teachers analyze from students ability on poetry then relate it to english syntax. Aim of this observation is students in school or university students with interpretation method as the research method. More or less this observation information depands on readers need with what they want to use or apply this information.Â